An Analytical Exploration of Factors Contributing to Increasing Turnover and Employee Retention Challenges in a Private Educational Institution - Columna, Farrah Jane; Garcia, Ferdinand (JPAIR Institutional Research, 2024)
This study examines the factors contributing to increasing turnover and retention challenges in a private educational institution in the Philippines. Using a mixed-methods approach, quantitative data were gathered using a descriptive-correlational methodology, while semi-structured interviews with current and former employees were used to acquire qualitative insights. Results reveal a very high level of turnover intention among respondents, with compensation and benefits and leadership and management found as the most significant factors, followed by work environment and culture and external factors. Age, marital status, and work status all show varying degrees of significance when it comes to perceived primary factors, while gender and length of service showed no significant influence on all the factors of turnover intention. Findings suggest the importance of addressing compensation and benefits, leadership and management, and work environment and external factor issues to enhance retention efforts in educational institutions.
Keywords: turnover intention; retention challenges; private educational institution; compensation and benefits; leadership and management; work environment; external factors; descriptive-correlational; Philippines